Across Economics and Psychology: Development and Validation of the In-Game Purchase Motivation Scale - Mirko Duradoni; Nicolò Della Maggiora; Giacomo Barbagallo; Mustafa Can Gursesli; Ginevra Niccolai; Andrea Guazzini (International Journal of Computer Games Technology)
This study is aimed at developing and validating a measurement scale for motivations behind in-game purchases, integrating economic and psychological aspects. Two separate samples of Italian gamers were used to develop a five-factor scale (utility, enjoyment, investment, reputation, and self-realization) capable of explaining a substantial portion of in-game spending behavior. In the first study, 573 gamers were recruited, and an initial four-factor scale measuring psychological motivations behind in-game purchases was internally and externally validated, explaining 5.4% of the variance in in-game purchases. In the second study, conducted with 284 gamers, the self-realization factor was added, increasing the scale’s explanatory power to 8% for the amount of money spent on in-game purchases. When controlling for variability attributed to the game type (i.e., analyzing just participants who spent money over a specific game), we observed an increase in the explanatory power of the scale from 5.4% to 12% for the initial four-factor model in Study 1 and from 8% to 27.5% for the evolved five-factor model in Study 2. The results indicate that gamers who purchase virtual items are driven by diverse psychological motivations that play a critical role in their spending behavior. This study provides a tool for identifying risk factors for potentially problematic purchase behaviors and offers insights for game developers and marketing professionals interested in optimizing user engagement strategies.